Symbolic structure of the post-Soviet transformations in Latvia and emigration: avoiding shame and striving for hope and confidence - Ķešāne, Iveta (Kansas State University, 2016)
This dissertation explores the case of emigration from Latvia towards the West after collapse of the Soviet Union. It takes the perspective of a particular cultural structure that came to dominate post-Soviet Latvia and adopts the vantage point of the state-society relationships this structure has cast. The central question of this study examines: what is the relationship between the cultural structure in post-Soviet Latvia and emigration towards the West? This study answers this question by contrasting Latvia’s civil discourse with emigrants’ and those who remain in Latvia personal narratives through the lens of cultural sociology that emphasizes the role of the symbolic realm, meaning making, and emotions. Research findings suggested that the post-Soviet cultural structure was dominated by "symbolic codes" (Alexander and Smith, 1993) or sharp divides such as West vs. East/Soviet, Right vs. Left, and Developed vs. Underdeveloped. Notably, symbolic codes of West, Right and Developed were constructed as “sacred” while their opposites were pushed out of "sacred" and ridiculed. These divides originated from such particular emotions as shame, confidence/pride and fear. Their meanings in the dominant transformation discourse and emotional origins were formative to the identity and modern state craft, and subjectivities in post-Soviet Latvia. These sharp divides between what is "sacred" in a community and what is not, came with "unintended consequences" (Weber, 2002). These divides and how they shaped the transformation discourse trumpeted misguided notion of the West, post-Soviet Latvia so eagerly wanted to resemble and belong to. Given this distorted notion of the West, the ruling elite fashioned environment where people not only lost hope for their better future in Latvia but began to lose their self-confidence - an important emotion for one’s "willingness to act" (Barbalet, 2004, p.83); and, as such, were more prone to emigration. Emigration for my respondents provided the space where West and Left were experienced as compatible despite their construction as incompatible in post-Soviet Latvia. Amidst confidence over their better future in their receiving countries, this gave to emigrants also a feeling of comfort, sense of self-confidence and empowerment.
Keywords: Post-Soviet transformations; Emigration; Culture; Symbolic codes; Emotions; Latvia